Unraveling the synthetic strategy, structure activity relationship of azetidinones: Insights into their multidrug and toxin extrusion protein (MATE transporter) inhibition facilitating drug development against MDR - Mal, Suvadeep; Mahapatra, Monalisa; Pakeeraiah, Kakarla; Panda, Preetesh Kumar; Sahoo, Jyotirmaya; Roy, Partha; Paidesetty, Sudhir Kumar (Bioorganic chemistry, 2025)
[Display omitted] •Chemistry of β-lactams/Azetidinones.•Aspects of different reactions viz., Staudinger’s, Gilman-Speeter, Kinugasa, Ugi-MCR etc. for synthesis of azetidinones.•Schematic representations of various reported azetidinones exploring anticancer and antimicrobial activities.•Structure activity relationship of the azetidinone bearing compounds with different molecular targets. Heterocyclic chemistry gathered a wide audience due to their presence in potential drug candidates and being attractive synthons initiating several retro-syntheses the organic as well as in medicinal chemistry fields. Among them, azetidinones have been a subject of discussion due to their serendipity, curiosity, versatility by Penicillin and Cephalosporins as β-lactam antibiotics. Despite possessing a large margin of biological activities, azetidinones mainly work as antimicrobial, interfering with bacterial cell-wall synthesis blocking transpeptidase. The structure and synthetic strategy of the azetidinone arouse its research interest in drug discovery pipeline. However, the extensive use of antibiotics in the modern era contributes to drug resistance that could only be counterbalanced involving hybridization approach. To explore the potency of the azetidinones, potent compounds found from literatures, have been screened through molecular docking against MATE transporter, targeting for prevailing multidrug resistance. The present review makes a sincere effort to compile the synthetic information and orientations involving hybridization of azetidinones with biologically active scaffolds emphasizing on antimicrobial and anticancer efficacies along with their MATE inhibition, keeping an eye upon the structure activity relationship in a systematic way. The study could motivate the researchers for developing a wide array of β-lactam derivatives more prominently targeting newer pathways to fight MDR.